PERAN PENYALURAN DANA PIHAK KETIGA BMT MUDA JATIM PADA PENINGKATAN KESEJAHTERRAAN PELAKU UMKM PERSPEKTIF MAQASHID SYARIAH - Puput Aristina; Tika Widiastuti (Universitas Airlangga, 2019)
Baitul Mal Wat Tamwil is an institution of Islamic micro finance which has a role and function to improve the economics potential and ability of members particularly and community commonly, to improve economic welfare. This research aims to find out the role of financing fund which is given by BMT to the prosperity of SME using perspective of maqasid shariah. The approach used is qualitative approach with case study method. Technique of gathering data uses direct interview to related informants. The result of this research show that BMT MUDA Jatim has played a role improving the properity of SME who has received financing funds by using perspective of maqasid shariah through any program Islamic finance.Keywords: Baitul Mal Wat Tamwil, Financing Fund, Prosperity, SME, Maqasid shariah